Viabilidade da utilização de óleo residual de fritura para a produção de biodiesel na cidade de Pouso Alegre, MG - Morais Neto, Honório José (2010)
This paper aimed at diagnosing the viability of using waste frying oil for the production of biodiesel in the city of Pouso Alegre, MG, Brazil, taking advantage of the facilities of the biodiesel plant of IFSULDEMINAS Machado campus. At first, a survey was conducted at the city hall for determining the units that generate waste oils and fats (WOF). Business establishments listed such as hotels, bars, restaurants, supermarkets, bakeries, food factories, street confectioners, buffets, among others, with a total of 266 generating units. There is also the potential use of WOF from the 37,587 homes of Pouso Alegre. With regard to commercial establishments, some use WOF to produce homemade soap, but all support the reuse of WOF and would participate in a collection program. An alternative was proposed for WOF collection: cooperatives or associations composed of former scavengers from a deactivated junkyard. To make the project viable, the use of the biodiesel plant of IFSULDEMINAS was chosen, once the Machado campus is only 72 km away from Pouso Alegre. This project is very important for the city, which is in a marked developmental stage, although facing aggression on the environment, generalized pollution, mainly in the sewage galleries which run into the Sapucaí River, one of the rivers of the Furnas Reservoir. According to a survey, approximately 840,000 liters of diesel per year can be produced from the WOF of Pouso Alegre (business establishments and homes), what would save an estimated amount of R$400,000.00 per year. These resources could be invested in other areas, such as environmental education and protection, health programs, work security, besides generation of income for the families. It is necessary to promote an awareness campaign among business establishments and the population in general for a qualified collection of recyclables. It can be concluded that the implementation of a project of such a magnitude, using WOF for biodiesel production in partnership with IFSULDEMINAS, would be the supporting tripod of sustainability: socially just, environmentally correct, and economically viable, thus benefiting the state, the city, a group of low-income workers, and above all the environment.